Genetically Modified Organisms (GMOs): cultured meat - Mohamed, Elizah; Jumadi, Nur Farah Nasuha; Azemi, Nur Asyiqin; Abd Aziz, Mohd Haiqal (Penerbit UTHM, 2022)
To satisfy the increasing demand for food nowadays, cultured meat is being introduced as a means for consumers who want to contribute to a better environment. This review aims to improve other people’s understanding of cultured meat’s role in sustainability. Cultured or in-vitro meat has the potential to produce faster and more efficiently than conventional meat. These techniques of growing muscle tissue from animal stem cells to produce meat would provide the needs while also preserving the environment in more environmentally friendly ways. However, cultured meat may be competitive with conventional meat and other meat substitutes, such as plant-based foods. Furthermore, consumer acceptance of cultured meat will be influenced by a variety of factors, with the majority of consumers disliking these unnatural foods. Hence, we discussed in this review from its production till the effects on other people in a variety of ways in order to eliminate these stereotypes.